2019
DOI: 10.1016/j.jmr.2019.06.002
|View full text |Cite
|
Sign up to set email alerts
|

A method for simulating level anti-crossing spectra of diamond crystals containing NV− color centers

Abstract: We propose an efficient method for calculating level anti-crossing spectra (LAC spectra) of interacting paramagnetic defect centers in crystals. By LAC spectra we mean the magnetic field dependence of the photoluminescence intensity of paramagnetic color centers: such field dependences often exhibit sharp features, such as peaks or dips, originating from LACs in the spin system. Our approach takes into account the electronic Zeeman interaction with the external magnetic field, dipole-dipole interaction of para… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…To gain insight into the spin dynamics, we also look at Level Crossings (LCs) of the spin states and determine under what conditions they are turned into Level Anti-Crossings (LACs). As discussed previously, LACs give rise to pronounced features in the magnetic field dependence of photoluminescence (PL) of color centers [37][38][39][40][41][42][43] and in ODMR spectra [43].…”
Section: Introductionmentioning
confidence: 99%
“…To gain insight into the spin dynamics, we also look at Level Crossings (LCs) of the spin states and determine under what conditions they are turned into Level Anti-Crossings (LACs). As discussed previously, LACs give rise to pronounced features in the magnetic field dependence of photoluminescence (PL) of color centers [37][38][39][40][41][42][43] and in ODMR spectra [43].…”
Section: Introductionmentioning
confidence: 99%
“…This paper deals with a curious bridge between the most humble magnetic field effect (MFE) curves, i.e., dependence of reaction yield on applied static magnetic field, and hyperpolarized NMR: additional sharp resonance-like lines that may occur against the smooth background of MFE due to genuine level crossings in the spin system of the radical pair. The lines were first discovered in a zero magnetic field (Anisimov et al, 1983;Fischer, 1983) and attributed to interference of pair states in the higher, spherical, symmetry conditions of a zero external field similar to the Hanle effect in atomic spectroscopy (Hanle, 1924). The zero field line, or low-field effect, was then put to the front as the possible physical mechanism of magnetoreception, and the re-search that followed was plenty.…”
Section: Introductionmentioning
confidence: 99%
“…Level crossing (Dupont-Roc et al, 1969;Silvers et al, 1970;Levy, 1972;Astilean et al 1994) and avoided crossing, or anticrossing (Eck et al, 1963;Wieder and Eck, 1967;Veeman and Van der Waals, 1970;Baranov and Romanov, 2001;Yago et al, 2007;Kothe et al, 2010;Ivanov, 2017, 2019), spectroscopy has long been an established tool in atomic and molecular spectroscopy as well as solid-state physics, providing structural information from specific (anti)crossing lines in nonzero fields, whose positions are determined by interactions shaping the energy levels of the system. For radical pairs purely spin level crossings at nonzero fields in MFE first appeared in calculations in an already cited paper (Anisimov et al, 1983), although they were not discussed as they were not observed in the accompanying experiments on radiolytically generated radical ion pairs. However, a year later this group published a theoretical work (Sukhenko et.…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical studies on spin bath induced spin relaxation processes have focused on strong environmental coupling regions where dynamical nuclear polarization can be achieved. 21,[43][44][45][46] Much less attention has been paid, however, to the calculation of spin bath assisted relaxation processes and related decay time T 1 of point defect qubits at general control parameter settings where spin flip-flops are suppressed to a large degree. In a very recent study, CCE method was generalized to describe spin flip-flops of a NV center interacting with a bath of 13 C nuclear spins.…”
Section: Introductionmentioning
confidence: 99%